ABOUT THE PRODUCTION OF FERTILIZER MIXTURE WITH THE USE OF TECHNOGENIC WASTE - Zhantasov K.T.,; Kozhakhmetova A.M.,; Dzhanmuldaeva Zh.K.,; Sarkulakova R.A.,; Almenova F.B., (Academic Scientific Journal of Chemistry, 2020)
Coal is one of the oldest fuels, and was the main source of energy until the middle of the XX century. Now, despite the active use of oil, gas, and uranium, the share of coal in global electricity production is about 40% (in China – 78%, in the US – 50%, in Russia – 19%). However, coal does not burn without a trace. In the process of its combustion, not only energy is generated, but also waste [1-2]. According to B. Tarchevsky's classification [3,4], ash dumps by origin belong to the group of garbage dumps. By addition, ash dumps can be either loose or tightly-tiled. The average size of ash deposits changes significantly only near the place where the pulp is released, and the size change is small in the rest of the ash dump [2]. After the end of operation of this container, ash dumps pollute the atmosphere, water, and soil. The situation that has developed in the world and domestic markets for mineral fertilizers and fertilizer mixtures makes a number of technological and technical requirements for obtaining high-quality products of the agroindustrial complex, is relevant, which formed the basis for the development and creation of an environmentally safe mixtures. The technology will allow you to: - to obtain a new nomenclature of fertilizer mixture containing magnesium and other micronutrients, as well as to develop a technological scheme for obtaining fertilizer mixture containing magnesium and other micronutrients; The results of innovative research will be used in the agricultural sector of the economy and in farms of the Republic of Kazakhstan.